1993
DOI: 10.1002/joc.3370130304
|View full text |Cite
|
Sign up to set email alerts
|

West African rainfall deficits and sea surface temperatures

Abstract: Comparisons between years of below average rainfall over West Africa, sea-surface temperatures (SST) over the Atlantic Ocean and the world ocean, and latitudinal positions of the Inter Tropical Convergence Zone (ITCZ) over the Atlantic Ocean show that the relationships depend mainly on the rainfall anomaly patterns. The well-known SST dipole (cold northern ocean and warm equatorial and southern ocean) is only apparent during those August months with below average Sudano-Sahelian rainfall and above average Guin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
40
0
5

Year Published

1997
1997
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(48 citation statements)
references
References 35 publications
(38 reference statements)
3
40
0
5
Order By: Relevance
“…Lamb, 1978aLamb, , 1978bHastenrath, 1984;Lough, 1986;Palmer, 1986;Wolter, 1989;Folland et al, 1986Folland et al, , 1991Lamb and Peppler, 1992;Janicot, 1992b;Fontaine and Bigot, 1993;Fontaine and Janicot, 1996;Fontaine et al, 1998). These relationships hold for both annual and interdecadal timescales (Hastenrath, 1990;Ward, 1998).…”
Section: Links With Sst Distributionsmentioning
confidence: 88%
“…Lamb, 1978aLamb, , 1978bHastenrath, 1984;Lough, 1986;Palmer, 1986;Wolter, 1989;Folland et al, 1986Folland et al, , 1991Lamb and Peppler, 1992;Janicot, 1992b;Fontaine and Bigot, 1993;Fontaine and Janicot, 1996;Fontaine et al, 1998). These relationships hold for both annual and interdecadal timescales (Hastenrath, 1990;Ward, 1998).…”
Section: Links With Sst Distributionsmentioning
confidence: 88%
“…A number of studies have shown that dry years with and without the rainfall dipole differ with respect to both circulation anomalies over west Africa and sea surface temperature (SST)-rainfall associations (Semazzi et al, 1988;Janicot, 1992b;Fontaine and Bigot, 1993;Fontaine et al, 1995;Janicot et al, 1996;Ward, 1998). Nicholson and Grist (2001) hypothesize that the dipole and dry patterns have fundamentally different causes.…”
Section: The Spatial Patterns Of Rainfall Variabilitymentioning
confidence: 99%
“…Research in dynamic tropical climatology over the last 20 years shows that Sea Surface Temperature (SST) on the regional and global scale strongly influences climate (Fontaine and Bigot 1993;Moron et al 1995;Bigot et al 1997). It is possible to characterise the relations between the monsoon rains and the SST more precisely.…”
Section: Conclusion: the Major Role Of Climatic Conditions And Their mentioning
confidence: 99%
“…The second mode presents an opposed distribution for the African continent and the ocean. A north-south tropical Atlantic 'dipole' has thus been found which oscillates between one mode and the other (Fontaine and Bigot 1993;Wotling et al 1995;Bigot et al 1997). An important research result has been to show that over recent millennia the spatial distribution of paleo-climatic anomalies over tropical Africa (more humid regions and more dry ones; Figure 6) and of SST on the neighbouring Atlantic, is very similar to the spatial distribution observed for the two dominant anomalies over the last four decades (Maley 1997;Maley et al 2000).…”
Section: Conclusion: the Major Role Of Climatic Conditions And Their mentioning
confidence: 99%